2010
DOI: 10.1111/j.1365-2362.2010.02398.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analysis of human plasma from haemodialysis patients

Abstract: 1-Methylinosine and two unknown molecules whose m/z at ESI-positive mode are 257·1033 and 413·1359 were found as effective candidate biomarkers to estimate adequate haemodialysis dose, which has to be confirmed in prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 16 publications
0
47
0
1
Order By: Relevance
“…Increasing interest has been directed toward the application of metabolite profiling to plasma from individuals with existing CKD or ESRD. [2][3][4][30][31][32] Here, we profile plasma obtained from individuals up to 8 years before disease onset, on the principle that non-GFR markers of renal metabolite handling may be sensitive indicators of incipient kidney dysfunction. Although metabolite profiling alone may not be sufficiently specific to identify individuals who go on to develop CKD, it may contribute to clinical models of CKD prediction that contain other variables.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing interest has been directed toward the application of metabolite profiling to plasma from individuals with existing CKD or ESRD. [2][3][4][30][31][32] Here, we profile plasma obtained from individuals up to 8 years before disease onset, on the principle that non-GFR markers of renal metabolite handling may be sensitive indicators of incipient kidney dysfunction. Although metabolite profiling alone may not be sufficiently specific to identify individuals who go on to develop CKD, it may contribute to clinical models of CKD prediction that contain other variables.…”
Section: Discussionmentioning
confidence: 99%
“…UPLC-based metabonomics was developed to analyze the plasma samples from end-stage renal disease patients. 1-Methylinosine was found to be an effective candidate biomarker to estimate adequacy of a hemodialysis regimen [77]. One study reported that urinary hypoxanthine was the most significant metabolite in children with nephrolithiasis.…”
Section: Chronic Kidney Disease (Ckd)mentioning
confidence: 99%
“…High-resolution mass spectrometry has revealed the accumulation of many compounds that do not appear in lists of known metabolites and are characterized only by molecular mass. [11][12][13][14][15][16] With the inclusion of such compounds, the number of reported uremic solutes will soon rise above 500.…”
Section: The Multiplicity Of Uremic Solutesmentioning
confidence: 99%